2009
DOI: 10.1016/j.transproceed.2009.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Association of Traditional and Genetic Risk Factors and New-Onset Diabetes Mellitus Following Kidney Transplantation

Abstract: Introduction New-onset diabetes mellitus, which occurs after kidney transplant and type 2 diabetes mellitus (T2DM), shares common risk factors and antecedents in impaired insulin secretion and action. Several genetic polymorphisms have been shown to be associated with T2DM. We hypothesized that transplant recipients who carry risk alleles for T2DM are “tipped over” to develop diabetes mellitus in the posttransplant milieu. Methods We investigated the association of genetic and traditional risk factors presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
3
22
0
2
Order By: Relevance
“…Few genetic polymorphisms appeared as negative association, such as SLC30A8, IGFBP2, HHEX, CDKN2A/B, PPARG, KCNJ11, and TCF7L2 (9,21). Our studies showed positive association towards rs7903146 and rs13266634 polymorphisms and not in accordance with the prior studies carried out in PTDM subjects in different ethnicities (9,15,21). The associations of diabetic diseases with rs7903146 and rs13266634 polymorphisms have been carried in Indian population (14,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Asupporting
confidence: 62%
See 2 more Smart Citations
“…Few genetic polymorphisms appeared as negative association, such as SLC30A8, IGFBP2, HHEX, CDKN2A/B, PPARG, KCNJ11, and TCF7L2 (9,21). Our studies showed positive association towards rs7903146 and rs13266634 polymorphisms and not in accordance with the prior studies carried out in PTDM subjects in different ethnicities (9,15,21). The associations of diabetic diseases with rs7903146 and rs13266634 polymorphisms have been carried in Indian population (14,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Asupporting
confidence: 62%
“…synthesis, storage, and secretion (14). Previous studies showed no association of rs13266634 polymorphism with PTDM in different ethnicities (9,15,21), as well with T2DM in Indian population (25,28). Chauhan et al, (27) and our earlier study (14) showed a positive association of rs13266634 polymorphism with PTDM.…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Amentioning
confidence: 43%
See 1 more Smart Citation
“…17 Several other risk factors, such as pre-transplant obesity, genetic disposition and certain infections, have also been identified or suggested. 18,22,23,30 Incidence rates of NODAT between 2 and 53% have been reported in the literature. 31 In the present study the one-year cumulative incidence was 15% and the diagnosis was made within 180 days after transplantation in nearly 95% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, several other risk factors such as age, pre-transplant weight, certain infections and genetic predisposition have also been identified or suggested. [18][19][20][21][22][23] To the best of our knowledge, the role of hyperparathyroidism in developing NODAT has not been studied. This association could have important implications in the assessment of the individual patient risk of NODAT and in how to handle hyperparathyroidism in transplanted patients.…”
Section: Introductionmentioning
confidence: 99%